EDITING MIDDLE ENGLISH PUNCTUATION. THE CASE OF MS EGERTON 2622 (FF. 136-152)' - Calle Martín, Javier; Miranda García, Antonio (International Journal of English Studies, 2009)
Traditionally, the study of mediaeval punctuation systems has been skipped by scholars in view of the lack of consistency in their use. However, specific studies have been recently published showing that the punctuation practice of mediaeval scribes was not that whimsical (Alonso-Almeida, 2002: Leimard, 1992; Rodríguez-Álvarez, 1998). In the present paper, a 15th-century arithmetical treatise housed in British Library, MS Egerton 2622 (S[ 136'-152') will be analysed with a twofold objective: a) to offer a detailed account of the use and function of Symbols in the ireatise; and b) to find the correspondence with modern punctuation.